Electrochemical Fluorination and Radiofluorination of Methyl(phenylthio)acetate Using Tetrabutylammonium Fluoride (TBAF). Issue 9 (1st January 2017) - Balandeh, Mehrdad; Waldmann, Christopher; Shirazi, Daniela; Gomez, Adrian; Rios, Alejandra; Allison, Nathanael; Khan, Asad; Sadeghi, Saman
Abstract : Electrochemical fluorination of methyl(phenylthio)acetate was achieved using tetrabutylammonium fluoride (TBAF). Electrochemical fluorination was performed under potentiostatic anodic oxidation using an undivided cell in acetonitrile containing TBAF and triflic acid. The influence of several parameters including: oxidation potential, time, temperature, sonication, TBAF concentration and triflic acid concentration on fluorination efficiency were studied. It was found that the triflic acid to TBAF concentration ratio plays a key role in the fluorination efficiency. Electrochemical fluorination resulted in formation of mono-fluorinated methyl 2-fluoro-2-(phenylthio)acetate verified by gas chromatography–mass spectrometry (GC-MS) and nuclear magnetic resonance (NMR) Spectroscopy. Under optimum conditions 44 ± 3% mono fluorination yield was obtained after a 30 min electrolysis. Electrochemical radiofluorination for the synthesis of methyl 2-[ 18 F]fluoro-2-(phenothio) acetate was also achieved with the same optimized electrochemical cell parameters where TBAF was first passed through an anion exchange resin containing fluorine-18. A radiochemical fluorination efficiency of 7 ± 1% was achieved after 30 min of electrolysis.